Social advertisement awareness and social media engagement attitude of consumers: an empirical examination. (15th December 2021) - Shanthi, R.; Rekha, M.; Priya, J. Bhanu
The society is witnessing an imperative and necessary requirement of social media platform to share their perception and attitude towards their daily lives. In this digital era the social advertisements are taken to the people through social media sites in the form of memes, posts, images etc. thus the study gains importance in this modern world measuring the media engagement in social advertisements. The purpose of this paper is to determine the consumer's social media engagement attitude towards social advertisement campaigns awareness. This study sample was 160 and convenience sampling technique had been used to collect the primary data from respondents through a structured questionnaire, with EFA having been applied to determine the dimensions of social media engagement attitudes of social advertisements campaigns. The study concludes, the role of social advertisements cannot be ignored or negotiated. It is very important to make these ads more effective to tackle the social issues.